Penerapan Model Pembelajaran Inkuiri Terbimbing (Guided Inquiry) Untuk Meningkatkan Keterampilan Mengkomunikasikan Pembelajaran IPA Pada Siswa Sekolah Dasar - Yunita Fitri Anggraeni; Kartono Kartono; Idam Ragil Widianto Atmojo (Universitas Sebelas Maret, 2019)
The purpose of this research is to improve communicating skills through GuidedInquiry model in Grade V students of Elementary School Year 2016/2017.This research wasconducted in three cycles. Each cycle consist of four phase namely: planning, implementation,observation, and reflection. The subjectof the research were the teacher and 34 students at thefifth grade of Elementary School Year 2016/2017. Data collection techniques used are theresults of observation, interviews, and documentation. The validity of the data used is thecontent validity. Data analysis used is interactive analysis model which has three componentthat is data reduction, data presentation, and conclusion. The result of the research shows thatthe application of the Guided Inquiry model can improve the communicating skill of grade Vstudents of Elementary School Year 2016/2017. On the pre-condition before the classroomaction research was conducted, verbal communication skillsthe students’ minimal learningcompleteness was 5,88%. Following the treatments with the Guided Inquirymodel, it became17,65% in Cycle I, 41,18% in Cycle 2, and 82,35% in Cycle III.Similarly, students'communication skills in writing on the pre-condition percentage of grade attainment of8,82%.Following the treatments with the Guided Inquirymodel, it became 32,35% in Cycle I, 58,82%in Cycle 2, and 82,35% in Cycle III.Therefore, it can be concluded that the Guided Inquirymodel could improvecommunicating skill of the students at the fifth grade of ElementarySchool Year 2016/2017.